Force output comparison betwen six U.S. collegiate athletic teams - Bazyler, C.; Beckham, G.; Gray, H.; Hornsby, G.; Kavanaugh, A.; MacDonald, C.; Mizuguchi, S.; Stone, M.; Stone, M. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The aim of the study was to compare allometrically scaled peak force and the force at 250 ms between six U.S. collegiate sport teams using isometric mid-thigh pull. Ninety subjects performed maximum effort of isometric mid-thigh pull to measure force output. The data were averaged within the teams, and statistically compared between teams using one-way ANOVA (p=.01). Significant difference was found that men`s soccer and baseball produced higher allometrically scaled peak force, and men`s soccer, tennis, and baseball produced higher allometrically scaled force at 250 ms. The data indicates that not all sports possess similar strength characteristics because of the nature of the sports, and observed separation between gender. Teams such as volleyball and baseball showed higher coefficient of variation due to the various positions within their sports.